Long-Term Building Renovation Strategies—F-TOPSIS Analysis of Solutions Applied in the Chosen European Union Countries - Edyta Plebankiewicz; Jakub Grącki (Buildings)
The article analyzes long-term renovation strategies in EU member countries using the F-TOPSIS method, focusing on chosen criteria such as CO2 emission reductions, renovation rates, energy savings, investment requirements, and overall strategy quality. High-performing countries, such as Finland and Spain, demonstrate the importance of clear targets, robust planning, and substantial financial commitments. In contrast, several countries show gaps in strategic detail or ambition, highlighting challenges in achieving EU climate neutrality goals. The methodology underscores the effectiveness of multi-criteria decision-making tools in assessing complex renovation strategies. The findings emphasize the need for harmonized metrics and innovative approaches, such as digital tools like building renovation passports.